2017
DOI: 10.1021/acs.orglett.7b00641
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Deprotection ofpara-Methoxybenzyl Ethers in a Flow Electrolysis Cell

Abstract: Electrochemical deprotection of p-methoxybenzyl (PMB) ethers was performed in an undivided electrochemical flow reactor in MeOH solution, leading to the unmasked alcohol and p-methoxybenzaldehyde dimethyl acetal as a byproduct. The electrochemical method removes the need for chemical oxidants, and added electrolyte (BFNEt) can be recovered and reused. The method was applied to 17 substrates with high conversions in a single pass, yields up to 92%, and up to 7.5 g h productivity. The PMB protecting group was al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 51 publications
0
46
0
Order By: Relevance
“…An application of this electrochemical process is the oxidative cleavage of para -methoxybenzyl (PMB) ethers. 278 Brown and co-workers recently detailed an electrochemical protocol for the removal PMB protecting group in flow reactors (Figure 17A). The reaction mass efficiency and atom economy scores of this deprotection process compare favorably with common chemical methods involving strong oxidants such as CAN; other common alcohol protecting groups were tolerated.…”
Section: Anodic Oxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…An application of this electrochemical process is the oxidative cleavage of para -methoxybenzyl (PMB) ethers. 278 Brown and co-workers recently detailed an electrochemical protocol for the removal PMB protecting group in flow reactors (Figure 17A). The reaction mass efficiency and atom economy scores of this deprotection process compare favorably with common chemical methods involving strong oxidants such as CAN; other common alcohol protecting groups were tolerated.…”
Section: Anodic Oxidationmentioning
confidence: 99%
“…The reaction mass efficiency and atom economy scores of this deprotection process compare favorably with common chemical methods involving strong oxidants such as CAN; other common alcohol protecting groups were tolerated. 278 Wang and co-workers demonstrated that the benzyl cation arising from direct anodic oxidations could be intercepted with water whereupon further oxidation of the resulting benzyl alcohol furnishes the ketone (Figure 17B). 279 This process is most effective for methylene units substituted with two arenes; lower yields were noted otherwise.…”
Section: Anodic Oxidationmentioning
confidence: 99%
“…It is a commercial large electrolysis flow cell designed for multigram scale syntheses composed of a spiral flow channel sandwiched in between carbon polymer and stainless-steel electrodes and separated by a polymer spacer (Author Anonymous, nd, 2020). The performance of the flow cell was exemplified by various reactions, such as the methoxylation of N-formylpyrrolidine and deprotection of PMB (para-methoxybenzyl) ethers (Green et al, 2016(Green et al, , 2017.…”
Section: Continuous Flow Chemistry and Flow Electrosynthesismentioning
confidence: 99%
“…[22][23][24] Electrochemical reactors with long spiral channels up to 2 m in length were subsequently developed to increase production rates to a few grams per hour. 13,19,25 However, the use of 2D planar electrodes requires that the reactor have a relatively large volume to achieve a high level of productivity.…”
Section: Introductionmentioning
confidence: 99%